REASONS AND METHODS OF ETHNIC CONFLICT SETTLEMENT: THEORETICAL ASPECT - Рябінін, Є.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The essence and reasons of ethnic conflict eare considered. The approaches of domestic and foreign scientists and experts as for defining of this phenomenon is analysed. In the process of the research different stages of ethnic conflicts are analysed. The author underlines that all ethnic conflicts in this or that region have their own reasons, thus have own settlement methods, tha’s why copying instruments and methods of conflict settlement is undesirable in order to avoid conflict escalation.